(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
In this research, the ecological quality of the lake Vēveru (Latvia, Rēzekne district) according to zooplankton was investigated. Lake Vēveru has a large sapropel deposit with rich reserves of sapropel. Removal of sapropel requires organization of spatio-temporal monitoring to control the state or disturbance of the existing ecosystems in the long term. Zooplankton samples were collected and analyzed using standard methods in the open pelagic and littoral zones of the lake in different seasons. Quantitative samples of zooplankton in each sampling site were collected from the surface water layer at the depth of 0.5 m by filtering 100 l of water through an Apstein-type plankton net (64 µ). Biodiversity of zooplankton taxa in Lake Vēveru shows that the food base of juvenile and planktophagous fish is sufficient. The Shannon index according to the diversity of zooplankton taxa ranges from 0.84 to 1.52 by abundance, from 1.52 to 2.21 by biomass.